1986
DOI: 10.1104/pp.81.1.177
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Highly Purified Fractions of Plasma Membrane and Tonoplast from the Same Homogenate of Soybean Hypocotyls by Free-Flow Electrophoresis

Abstract: A procedure is described whereby highly purified fractions of plasma membrane and tonoplast were isolated from hypocotyls of dark-grown soybean (Glycine max L. var Wayne) by the technique of preparative free-flow electrophoresis. Fractions migrating the slowest toward the anode were enriched in thick (10 nanometers) membranes identified as plasma membranes based on ability to bind N-1-naphthylphthalamic acid (NPA), glucan synthetase-II, and KV-stimulated, vanadate-inhibited Mg2e ATPase, reaction with phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 13 publications
(18 reference statements)
6
43
0
Order By: Relevance
“…With plant Golgi antibodies then, as now, commercially unavailable, enzyme assays were the primary means of determining fraction composition. Profiling by enzyme assays was not sufficiently precise or efficient for tracking lower-abundance Golgi proteins amidst a relatively complex background of contaminants, although the distribution of enzyme activities reported by (Sandelius et al, 1986) are broadly consistent with later proteomic analyses. The first isolation of plant Golgi membranes has depended on both FFE and proteomic advances (Parsons and Heazlewood, unpublished data).…”
Section: Free Flow Electrophoresis (Ffe) Purification Of Golgisupporting
confidence: 51%
See 1 more Smart Citation
“…With plant Golgi antibodies then, as now, commercially unavailable, enzyme assays were the primary means of determining fraction composition. Profiling by enzyme assays was not sufficiently precise or efficient for tracking lower-abundance Golgi proteins amidst a relatively complex background of contaminants, although the distribution of enzyme activities reported by (Sandelius et al, 1986) are broadly consistent with later proteomic analyses. The first isolation of plant Golgi membranes has depended on both FFE and proteomic advances (Parsons and Heazlewood, unpublished data).…”
Section: Free Flow Electrophoresis (Ffe) Purification Of Golgisupporting
confidence: 51%
“…Plant homogenates were first subjected to FFE some decades ago (Kappler et al, 1986;Sandelius et al, 1986;Bardy et al, 1998) but these first forays demonstrated little potential for Golgi isolation. With plant Golgi antibodies then, as now, commercially unavailable, enzyme assays were the primary means of determining fraction composition.…”
Section: Free Flow Electrophoresis (Ffe) Purification Of Golgimentioning
confidence: 99%
“…The identification of the tonoplast through the different fractions obtained by free-flow electrophoresis of microsomal membranes was previously achieved by membrane thickness measurements and nitrate sensitive ATPase activity (25). The most electronegative fraction (fraction A) was found to consist of highly pure tonoplast vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…a ATPase activity was measured in the presence of 0.02% Triton X-1 00, the level of inhibitors was as for Table I. glucan synthetase II (25). A similar spectrum of markers is not available for the vacuolar membranes of plant cells (3).…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous polymer two-phase partition and freeflow electrophoresis not only result in highly purified preparations but also discriminate between membrane vesicles of opposite orientation (Larsson et al, , 1988Sandelius et al, 1986;Canut et al, 1987). The uncritical use of single biochemical markers for assessing the purity of plasma membrane fractions has often been questioned and additional methods, such as surface labelling and EM observation, have been used in order to provide confirmatory evidence of plasma membrane purification (Boss & Ruesink, 1979 ;Bowman et al, 1981;Scarborough, 1975;Sandelius et al, 1986). Additionally, limited 'attention to markers of other intracellular organelles which may contaminate plasma membrane fractions has compromised the degree of purity of many preparations.…”
Section: Introductionmentioning
confidence: 99%